2006
DOI: 10.2166/wst.2006.412
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and evaluation of nitrogen removal performance in subsurface flow and free water surface constructed wetlands

Abstract: With the aim of protecting drinking water sources in rural regions, pilot-scale subsurface water flow (SSF) and free water surface flow (FWS) constructed wetland systems were evaluated for removal efficiencies of nitrogenous pollutants in tertiary stage treated wastewaters (effluent from the Pasaköy biological nutrient removal plant). Five different hydraulic application rates and emergent (Canna, Cyperus, Typhia sp., Phragmites sp., Juncus, Poaceae, Paspalum and Iris) and floating (Pistia, Salvina and Lemna) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…NH 3 -N concentration in the effluent increased owing to the wastewater being directly introduced to the depth of 50 cm. This result suggested that shorter path of the sewage would result in the incomplete nitrification, which was in agreement of other studies [19,31]. Zhang et al [32] noted that NO 2 -N concentration in the effluent would be between 0.1 and 0.5 mg/L, thus indicating nitrification-denitrification process performed successfully in the subsurface infiltration system.…”
Section: Discussionsupporting
confidence: 90%
“…NH 3 -N concentration in the effluent increased owing to the wastewater being directly introduced to the depth of 50 cm. This result suggested that shorter path of the sewage would result in the incomplete nitrification, which was in agreement of other studies [19,31]. Zhang et al [32] noted that NO 2 -N concentration in the effluent would be between 0.1 and 0.5 mg/L, thus indicating nitrification-denitrification process performed successfully in the subsurface infiltration system.…”
Section: Discussionsupporting
confidence: 90%
“…Also, as noticed for BOD and TSS, CW5 did not provide any remarkable additional TKN removal (Figure 4). Removal coefficients (K NT20 ) were calculated (data not included) based on (Brix 1997;Kadlec 2004;Sousa et al 2004;Tunç siper et al 2006). In general, the CW showed 2 -4 log unit of E. coli reduction, producing effluents with 10 2 -10 4 E. coli per 100 mL (geometric means), however in a much less stable rate than the ponds ( Figure 5).…”
Section: Nutrients Removal and Biomass Productionmentioning
confidence: 99%
“…Kadlec and Knight (1996) had summarized the nitrogen removal equations of modeling the constructed wetland (Table 2). Tunçsiper et al (2006) simulated removal efficiencies of nitrogenous pollutants in SSF and FWS constructed wetland systems. Two types of the models (first-order plug flow and multiple regressions) were used to evaluate the system performances.…”
Section: Introductionmentioning
confidence: 99%